Economics of salt-induced land degradation and restoration - Qadir, Manzoor; Quillérou, E.; Nangia, V.; Murtaza, G.; Singh, M.; Thomas, Richard J.; Drechsel, Pay; Noble, A.D. (Wiley, 2014)
Food security concerns and the scarcity of new productive land have put productivity enhancement of degraded lands back on the political agenda. In such a context, salt-affected lands are a valuable resource that cannot be neglected nor easily abandoned even with their lower crop yields, especially in areas where significant investments have already been made in irrigation and drainage infrastructure. A review of previous studies shows a very limited number of highly variable estimates of the costs of salt-induced land degradation combined with methodological and contextual differences. Simple extrapolation suggests that the global annual cost of salt-induced land degradation in irrigated areas could be US$ 27.3 billion because of lost crop production. We present selected case studies that highlight the potential for economic and environmental benefits of taking action to remediate salt-affected lands. The findings indicate that it can be cost-effective to invest in sustainable land management in countries confronting salt-induced land degradation. Such investments in effective remediation of salt-affected lands should form part of a broader strategy for food security and be defined in national action plans. This broader strategy is required to ensure the identification and effective removal of barriers to the adoption of sustainable land management, such as perverse subsidies. Whereas reversing salt-induced land degradation would require several years, interim salinity management strategies could provide a pathway for effective remediation and further showcase the importance of reversing land degradation and the rewards of investing in sustainable land management.